IMPLEMENTATION OF VIRTUAL INDUSTRIAL WORK SIMULATION TO ENHANCE VOCATIONAL SCHOOL STUDENTS’ INTERNSHIP READINESS IN THE DIGITAL ERA (International Journal of Cultural and Social Science, 2026)
Digital technologies demand improved internship readiness among vocational students. This study evaluates the implementation of a Virtual Industrial Work Simulation (VIWS) to enhance internship preparedness for vocational high school learners. Using a research-and-development approach, VIWS was created with industry-based task scenarios, an interactive interface, and modules assessing technical skills and soft skills. A pilot involving 60 technical-stream students collected pre- and post-test performance data, participant perception surveys, observations, and interviews with teachers and industry partners. Results indicate a significant improvement in internship readiness scores (mean increase 28%), higher self-efficacy, and gains in problem-solving and team communication. Users and industry partners rated the simulation as relevant and usable; main challenges were infrastructure (connectivity and devices) and curriculum alignment. VIWS is recommended as a complementary measure to workplace practice, with integration into curricula, educator training, industry collaboration, and infrastructure development to ensure equitable access.